Environmental Influences on Patient Presentations: Considerations for Research and Evaluation at Mass-Gathering Events. Issue 5 (9th September 2019) - Hutton, Alison; Ranse, Jamie; Gray, Katherine L.; Turris, Sheila A.; Lund, Adam; Munn, Matthew Brendan
Abstract: Aim: This paper discusses the need for consistency in mass-gathering research and evaluation from an environmental reporting perspective. Background: Mass gatherings occur frequently throughout the world. Having an understanding of the complexities of mass gatherings is important to inform health services about the possible required health resources. Factors within the environmental, psychosocial, and biomedical domains influence the usage of health services at mass gatherings. A minimum data set (MDS) has been proposed to standardize collection of biomedical data across various mass gatherings, and there is a need for an environmental component. The environmental domain includes factors such as the nature of the event, availability of drugs or alcohol, venue characteristics, and meteorological factors. Method: This research used an integrative literature review design. Manuscripts were collected using keyword searches from databases and journal content pages from 2003 through 2018. Data were analyzed and categorized using the existing MDS as a framework. Results: In total, 39 manuscripts were identified that met the inclusion criteria. Conclusion: In collecting environmental data from mass gatherings, there must be an agreed-upon MDS. A set of variables can be used to collect de-identified environmental variables for the purpose of making comparisons across societies for mass-gathering events (MGEs).